MENINGKATKAN HASIL BELAJAR SISWA MTs ALKHAIRAAT KALUKUBULA KELAS VIIA PADA MATERI OPERASI HIMPUNAN DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE - Rusmin Y Ma'bud; Samsul B. Liasi; Ni Komang Rollicking (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2018)
The purpose of this study is to describe the application of the cooperative learning model type Think-Pair Share that can improve student learning outcomes in set operations in class VII A MTs Alkhairaat Kalukubula. This type of research is class action research which refers to the design of Kemmis and Mc. Taggart, namely planning, action, observation, and reflection. The subject of this study was VII grade A MTs Alkhairaat Kalukubula students. Data collection techniques were obtained through observation, written tests, interviews and field notes. This study consisted of two cycles, and each cycle was carried out in two meetings. The results showed that the application of the cooperative learning model type Think-Pair Share can improve student learning outcomes in set operating material in class VIIA MTs Alkhairaat Kalukubula by following phases, namely: (1) giving orientation, (2) think, (3) pair, (4) share, and (5) award.